Gold-catalyzed facile synthesis and crystal structures of benzene-/naphthalene-based bispentalenes as organic semiconductors - Sekine, Kohei; Schulmeister, Jürgen; Paulus, Fabian; Goetz, Katelyn; Rominger, Frank; Rudolph, Matthias; Zaumseil, Jana; Hashmi, A. Stephen K. (Chemistry - a European journal, 2019)
The gold-catalyzed facile synthesis of U-shaped and S-shaped bispentalenes is described from easily available tetra(arylethynyl)-benzenes and -naphthalenes. The optoelectronic and transistor properties were also investigated. The selectivity between the U-shaped and S-shaped bispentalene isomers can be tuned by the bulkiness of the ligand and the substrates. The S-shaped naphthalene-based bispentalene shows a one-dimensional face-to-face packing pattern in solid state and a good hole mobility, indicating that the S-shaped bispentalene core is highly suitable for transistor applications. The gold-catalyzed annulation of tetraynes provides a useful protocol in the synthesis of bispentalenes for organic semiconductors.